Exploring needs, perceptions, and preferences towards exercise video among overweight individuals - a qualitative study [version 4; peer review: 1 approved, 2 approved with reservations] - Rajagopal Kadavigere; Tulasiram Bommasamudram; K Vaishali; Samuel A. Pullinger; Shivashankara K. N.; Suresh Sukumar; Shishira K B; Praveen Hoogar (F1000Research)
Background The number of overweight people (BMI 25–29.9kg.m-2) in the world is increasing, which increases the risk of health problems and psychological difficulties. To reduce these risks, it is imperative to address unhealthy habits including food and exercise. This qualitative study aimed to explore the needs, perceptions, and preferences of overweight individuals on tailored exercise programs that incorporate educational videos. Methodology Forty Individuals between the age of 18-30 years with a BMI of 25-29.9kg.m-2 were included in the study using Purposive sampling from October 2023 to November 2023. Semi-structured in-depth interview was conducted for 45-60 minutes approximately among both active and inactive overweight individuals by a researcher trained in qualitative research. These interviews were audio-recorded and transcribed verbatim. Thematic analysis was performed using inductive and deductive approaches to identify the recurrent patterns, themes, and insights in the transcribed interviews. Results 8 themes, such as lifestyle factors, exercise explorations, holistic wellbeing and 44 subthemes emerged from the analysis, helping to shed light on the needs, perceptions, and preferences that overweight individuals experience when it comes to their preference for a customized exercise program provided through educational video. The participants wanted personalized regimens that catered to their requirements and levels of fitness. Conclusion In summary, the findings emphasize the value of educational videos that are easy to use, visually appealing, and supported by science. These videos should emphasize technique, varying levels of difficulty, and brief sessions.